Eksplorasi Teknik Pengambilan Gambar dalam Film untuk Menghadirkan Aroma pada Visual - Maharsidik, Beto (Mahesa Research Center, 2025)
The exploration of shooting techniques in film has the potential to deliver a rich sensory experience, including triggering the sense of smell through visuals. This article aims to identify and analyze cinematic techniques that can create the illusion of scent in film, specifically through the application of sensory shots. This technique involves the use of close-up compositions to highlight subtle details such as steaming steam, the play of light to emphasize the texture and freshness of the object, and the slow movement of the camera and the movement of the camera closer towards the object to reinforce the impression of the presence of scent, as if the viewer is approaching to kiss directly. Using qualitative methods and textual analysis approaches, this study reviewed a number of culinary-themed films, including Tabula Rasa (2014) and Little Forest (2018), to observe certain visual ways of presenting the impression of aroma on the screen. In addition to the culinary genre, this technique also has great potential to be applied in the thriller or horror genre, for example, to build an atmosphere of tension or disgust through an emphasis on textures, liquids, and other visual details that provoke the audience's sensory reactions. This article explores cinematic strategies for communicating taste and scent through visual media, thereby creating a richer and more immersive cinematic experience. The results of this study are expected to expand the understanding of cinematic techniques as a medium of sensory communication across genres, especially in culinary films and other genres that rely on the intensity of sensory experiences.